Wiley Encyclopedia of Biomedical Engineering 2006
DOI: 10.1002/9780471740360.ebs1344
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Data Analysis

Abstract: Microarray analysis is an emerging field, simultaneously harnessing advances in semiconductor manufacturing, biochemistry, medicine, computation, and algorithms research. Microarrays now provide a platform for an unprecedented genome‐wide view of a biological sample. Microarray analysis makes use of the vast amounts of data that the microarray platform provides. It is through the intelligent combination of mathematical algorithms and clinical validation that microarray analysis provides a real opportunity to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…In the case of harshness and sensitivity, they were also roughly comparable to findings for 3-year-olds reported by Olson et al (2005). The similarity of findings at first and fifth grades is not surprising given that children who manifest externalizing behavior early in life often exhibit such behaviors through middle childhood (Campbell, 2002; Moffitt, 2006; Tremblay, 2000) and given that the three aspects of parenting examined in the two studies showed substantial stability as well. These general patterns granted, later maternal sensitivity appears to be more strongly associated with fifth-grade self-control than early maternal sensitivity was with first-grade self-control.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…In the case of harshness and sensitivity, they were also roughly comparable to findings for 3-year-olds reported by Olson et al (2005). The similarity of findings at first and fifth grades is not surprising given that children who manifest externalizing behavior early in life often exhibit such behaviors through middle childhood (Campbell, 2002; Moffitt, 2006; Tremblay, 2000) and given that the three aspects of parenting examined in the two studies showed substantial stability as well. These general patterns granted, later maternal sensitivity appears to be more strongly associated with fifth-grade self-control than early maternal sensitivity was with first-grade self-control.…”
Section: Discussionsupporting
confidence: 72%
“…Although externalizing problems manifest in early childhood tend to persist into middle childhood (Hill, 2002; Moffitt, 2006), it remains unclear whether externalizing problems observed in fifth grade continue to reflect experiences in the preschool years. Some theories (e.g., attachment, social learning) suggest that experiences early in life may be especially important, as they establish a base for attitudes about social relationships, expectancies pertaining to control, and motivational patterns.…”
Section: The Emergence Of Self-controlmentioning
confidence: 99%
See 1 more Smart Citation
“…The maturity gap perspective provides rationale that the TDBD phenomenon may apply to changing social status profiles. From this perspective, adolescents confer status to students who engage in noncompliant behavior as it represents asserting independence (Moffitt, 1993, 2006). The root cause of this dynamic is that adolescents have limited responsibilities and decision-making opportunities and turn to noncompliant behavior as means for asserting autonomy.…”
Section: The Importance Dimensions and Overlap Of Social Status Durin...mentioning
confidence: 99%